2010
DOI: 10.1590/s1808-18512010000300017
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic adrenal pheochromocytoma to the thoracic spine

Abstract: To report on a case of pheochromocytoma metastases to the spine occurring more than 20 years after initial diagnosis. A 34-year-old female with a history of metastatic pheochromocytoma diagnosed at age 12 presented with weakness, heart palpitations, and circumferential back pain of five months duration. The patient had undergone multiple laparatomies for abdominal and hepatic metastases. Work-up revealed a destructive lesion at T9. After two weeks of preoperative phenoxybenzamine to control her hypertension, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…There have been case reports on malignant PCC/PGL in which EBRT was delivered to unknown total doses. In these cases, irradiation was delivered to the primary tumor or metastatic sites with varying symptomatic control and most often with progression of local and distant disease ( 2 6 ). However, these reports may be of limited utility especially in PCC/PGL, given results from a 1978 literature review, which concluded that radiation therapy is beneficial for symptomatic relief of bone and lymph node metastases only at high doses ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…There have been case reports on malignant PCC/PGL in which EBRT was delivered to unknown total doses. In these cases, irradiation was delivered to the primary tumor or metastatic sites with varying symptomatic control and most often with progression of local and distant disease ( 2 6 ). However, these reports may be of limited utility especially in PCC/PGL, given results from a 1978 literature review, which concluded that radiation therapy is beneficial for symptomatic relief of bone and lymph node metastases only at high doses ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“… 20 Scalfani et al reported excision of the extradural component of a thoracic metastatic pheochromocytoma in a patient with disseminated disease who died 26 months after surgery. 21 …”
Section: Resultsmentioning
confidence: 99%
“…Several case reports have demonstrated that intralesional surgical resection for functional tumor spinal metastasis has some benefit; however, the prognosis often remains dismal. 20 21 …”
Section: Discussionmentioning
confidence: 99%
“…No hemodynamic instability was noted in the patient. Similarly, Scalfani et al 16 reported an excision of the extradural component of a metastatic pheochromocytoma in the thoracic spine of a patient with widespread systemic disease. Although the authors did not report any postoperative complications, this patient died of disease 26 months after surgery.…”
Section: Discussionmentioning
confidence: 96%